Energy analysis and life cycle assessment of a thermal energy storage unit involving conventional or recycled storage materials and devoted to industrial waste heat valorisation. (1st January 2022) - Lalau, Yasmine; Al Asmi, Ibrahim; Olives, Régis; Dejean, Guilhem; Meffre, Antoine; Py, Xavier
Abstract: Any system intending to improve the environmental performances of a process should be assessed by a Life Cycle Assessment. This work draws up the environmental profile of the heat provided by a storage system recovering industrial waste heat at high temperature (500 °C) through 5 selected indicators: Cumulative Energy Demand, Global Warming Potential, abiotic depletion potential, particle matter and freshwater eutrophication. The calculated indicators were compared to those of the fossil fuel substituted by the recovered heat, that is to say natural gas, and proved to be reduced. Then, the environmental payback times were calculated; and an energetic profitability evaluation by the Energy Returned on Investment expanded on the profile. Besides, the influence of operating conditions variations was investigated through a parametric study. An optimal number of cycles to provide the same amount of energy may be defined, as a compromise between the abiotic resource depletion potential reduction with smaller tanks performing more cycles and the energy returned on investment deteriorated with the operational energy consumption increased due to higher pressure drop with smaller tank diameter. The most rewarding environmental performances concerned the Cumulative Energy Demand, Global Warming Potential indicators of the provided heat, about 1.2 kgCO2 -eq and 65 MJ-eq per kWh (payback time lower than 3 months), and the Energy Returned on Investment that doubled compared to natural gas, e.g. reached a value of 55. The positive effect of using recycled storage materials on the resource depletion indicator were enlightened, notably when the operating conditions strayed from the reference case. Highlights: LCA and EROI analysis of a real TES system for waste heat recovery are performed. The benefits of waste-based TES material are enlightened. The operating conditions variations influence are studied. The provided heat has low environmental impacts: 1.2 kgCO2 -eq and 65 MJ-eq per kWh.